PARE0030 PEER SUPPORT OF PATIENT AND PUBLIC INVOLVEMENT AND ENGAGEMENT IN RESEARCH: THE 'RUG-BUDDY'. (2nd June 2020) - Higginbottom, A.; ,; Rhodes, C.; Campbell, L.; Blackburn, S.
Abstract : Background: Since 2006, The School of Primary, Community and Social Care, Keele University has a long standing commitment to Patient and Public Involvement and Engagement (PPIE) in research. The School's Research User Group (RUG) has 133 members in January 2020, compared to 80 members in September 2016. Supporting the practical and emotional needs of a growing number of RUG members to support their long-term involvement is of prime importance. Arising from Keele's role as a test bed site for the new UK Public Involvement Standards, a new peer support role (the 'RUG-Buddy') was co-produced to facilitate the support of RUG members. Objectives: The RUG-Buddy is a peer support and mentoring scheme. More experienced RUG members attend research meetings with less experienced members to provide support and reassurance. The scheme aims to provide: A welcoming and friendly environment for RUG members Extra support for all RUG members before, during and after research meetings Help new RUG members ease into public involvement Support with discussions between researchers and RUG members, e.g. avoiding research jargon Reassurance to new members - learning from those with greater experience of public involvement Someone to talk to and confide in from people who have personal experience of PPIE Practical advice on completing payment forms, parking issues, etc. Methods: Peer support is provided by a panel of existing RUG members who have substantial experience of PPIE in research. This is an additional method of supporting the RUG members alongside support provided by the School's PPIE team. RUG-Buddies will be supported in their role by the PPIE team and provided with an induction and training. RUG-Buddies are offered payment for their time and have their travel expenses reimbursed. The RUG-Buddies scheme will be piloted during an initial 6-month period, after which it will be reviewed, with feedback from RUG-Buddies and RUG members. Results: A role description for the RUG-Buddy role has been coproduced by Keele's PPIE team and its RUG Steering Group (Table 1 ). A panel of 10 RUG members have been recruited for the RUG-Buddy role and have received an induction and training (e.g. Health and Safety, Information Governance). RUG-Buddies have provided support to and attended research meetings with other RUG members. The RUG-Buddy role will be reviewed in September 2020. Conclusion: The RUG-Buddy is an innovative peer support scheme to support the involvement of patients and the public in research. The support provided by RUG-Buddies offers a different perspective from people with real-life experience of involvement in research. It is anticipated that this additional support will enrich the experience of RUG members and facilitate a more welcoming and conducive environment for active and meaningful public involvement. Furthermore, it has also provided an opportunity for the RUG-Buddies to gain valuable new skills and also give something back to the PPIE team and researchers who have supported their own involvement for many years. Acknowledgments: This project is funded by the National Institute for Health Research (NIHR) School for Primary Care Research (project reference 440). Thank you to the Keele Research User Group for all their great work Disclosure of Interests: None declared